Pengaruh Disiplin dan Motivasi Kerja Terhadap Kinerja Pegawai PT Gayung Kencana Sakti Kota Depok - Gustian Aulia Suherlin (Jurnal Manajemen Riset Inovasi, 2023)
This study aims to determine how much influence work discipline (X1) has on employee performance (Y) at PT Gayung Kencana Sakti, and to find out how much work motivation has on employee performance at PT Gayung Kencana Sakti. As well as to find out how much influence Work Discipline (X1) and Work Motivation (X2) have on the performance of employee of PT Gayung Kencana Sakti simultaneously.This research method uses a quantitative method with a questionnaire distribution technique to obtain primary data from employees of PT Gayung Kencana Sakti with a saturated sample of 30 respondents.The results of the simultaneous analysis prove that work discipline and work motivation are proven to have a positive and significant effect on performane together with a calculated F count of 27,905 greater than F table 3,32 or the equation 27,905 > 3,32 a significant value of 0,000 where the value is smaller than with the equation (0,000 < 0,005). With a coefficient of determination of 0,674 or 67,4%, it is in accordance with the standard measurement of the simultanoues test, namely Ha is accepted Ho is rejected.